2013
DOI: 10.1007/s00401-013-1096-7
|View full text |Cite
|
Sign up to set email alerts
|

α-Synucleinopathy associated with G51D SNCA mutation: a link between Parkinson’s disease and multiple system atrophy?

Abstract: We report a British family with young-onset Parkinson’s disease (PD) and a G51D SNCA mutation that segregates with the disease. Family history was consistent with autosomal dominant inheritance as both the father and sister of the proband developed levodopa-responsive parkinsonism with onset in their late thirties. Clinical features show similarity to those seen in families with SNCA triplication and to cases of A53T SNCA mutation. Post-mortem brain examination of the proband revealed atrophy affecting frontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
318
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 391 publications
(342 citation statements)
references
References 83 publications
(105 reference statements)
9
318
0
1
Order By: Relevance
“…Both immunohistochemical (17,22) and proteomic studies (20) have shown that α-Syn within LBs and other different inclusions can be ubiquitinated and phosphorylated at S129 and/or at Y125 (17,22,30,31). Interestingly, exogenously prepared α-Syn fibrils are rapidly ubiquitinated and phosphorylated at S129 upon internalization in mammalian cell lines and following stereotaxic injection and uptake by neurons in mouse brain (32,33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both immunohistochemical (17,22) and proteomic studies (20) have shown that α-Syn within LBs and other different inclusions can be ubiquitinated and phosphorylated at S129 and/or at Y125 (17,22,30,31). Interestingly, exogenously prepared α-Syn fibrils are rapidly ubiquitinated and phosphorylated at S129 upon internalization in mammalian cell lines and following stereotaxic injection and uptake by neurons in mouse brain (32,33).…”
Section: Resultsmentioning
confidence: 99%
“…Despite several reports demonstrating that ubiquitinated α-Syn is also phosphorylated at its C terminus (S129 and Y125) (17,22,30,31), the interplay across these modifications has not previously been investigated. Our results demonstrate that the effect of phosphorylation at Y125 on α-Syn aggregation is dependent on the length of the poly-Ub chain.…”
Section: Discussionmentioning
confidence: 99%
“…other neurodegenerative disorders (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). α-Synuclein is largely cytosolic, but readily binds to membranes, and associates with synaptic vesicles in the presynaptic terminal (22,23).…”
Section: α-Synuclein Multimerizes On Phospholipid Surfaces In An Antimentioning
confidence: 99%
“…Point mutations in α-synuclein (A30P, E46K, H50Q, G51D, and A53T) as well as α-synuclein gene duplications and triplications produce early-onset Parkinson's disease (PD) (4)(5)(6)(7)(8)(9)(10). Moreover, α-synuclein is a major component of intracellular protein aggregates called Lewy bodies, which are pathological hallmarks of neurodegenerative disorders such as PD, Lewy body dementia, and multiple system atrophy (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…In Parkinson disease (PD), a causative role for αS has been established via the discovery of mutations in the αS gene SNCA resulting in autosomal-dominant PD (4)(5)(6)(7)(8)(9)(10)(11). Although αS inclusions (e.g., Lewy bodies) are the hallmark pathology of PD, how they contribute to disease pathogenesis remains controversial (1,3,4,12).…”
mentioning
confidence: 99%